Multiconnectivity for Mobility Robustness in Standalone 5G Ultra Dense Networks with Intrafrequency Cloud Radio Access - Tesema, Fasil B.; Awada, Ahmad; Viering, Ingo; Simsek, Meryem; Fettweis, Gerhard P. (Wireless Communications and Mobile Computing, 2017)
Capacity and ultra-reliable communication are some of the requirements for 5th generation (5G) networks. One of the candidate technologies to satisfy capacity requirement is standalone Ultra Dense Network (UDN). However, UDNs are characterized by fast change of received signal strength that creates mobility challenges in terms of increased handovers and connection failures. In this paper, a low layer multiconnectivity scheme is presented for standalone UDN aiming at ultra-reliable communication that is free of interruptions from handover procedures and connection failures. Furthermore, the problem in managing of the set of serving cells, that are involved in multiconnectivity for each user, is formulated. By using numerical method, feasible scheme for management of the set of serving cells is derived. Performance of the proposed multiconnectivity scheme is evaluated and compared against single connectivity. It is shown that the proposed multiconnectivity scheme outperforms single connectivity considerably in terms of connection failures and cell-edge throughput.